Canine and Human Red Blood Cells: Biochemical Mechanisms for the Control of Heat Dissipation - Annamaria Russo; Giuseppe Tancredi Patanè; Stefano Putaggio; Ester Tellone; Silvana Ficarra; Davide Barreca; Giuseppina Laganà (Stresses)
Dogs, unlike humans, are equipped with a reduced number of sweat glands, which makes it difficult for them to dissipate heat, especially in conditions of intense activity that lead to a significant increase in body temperature. The study aims to investigate the metabolic differences between canine and human red blood cells (RBCs) and the hemoglobin (Hb) functionality focusing on their roles in heat dissipation. In detail, we evaluated the Band 3 protein (AE1) kinetic flux by observing that in canine red blood cells the anion exchange rate is higher than in humans (Rate Constant: 0.0438 min−1 and 0.012 min−1, respectively). Furthermore, we investigated the rate of ATP production and release to evaluate the possible variation of nucleotide concentration in the two species, observing a lower intracellular ATP concentration (101.80 μM and 297.90 μM) but a higher ATP release (3 μM and 2.65 μM) in canine RBCs compared to humans respectively. Subsequently, we evaluated the involvement of canine hemoglobin in heat dispersion; in detail, the ΔH= −5.15 Kcal/mol recorded in dog hemolysate at pH 7.5 shows an exothermic Hb-O2 bond that may be useful for further dispersing heat from the lungs. The peculiar oxygen-binding properties of dog Hb may also promote oxygen release in hyperventilation characterized by alkaline pH.